STRATEGI MARKETING PUBLIC RELATIONS DALAM MENARIK MINAT PELANGGAN DI HOTEL GRAND ELITE PEKANBARU - Triyani Merdeka Wati; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
service accomodate, eat and drink, and also the other service. With the increasing development of four stars hotel in Pekanbaru, much less affected Grand Elite Hotel to build a strategy to attract costumer interest. The problem identification in this research is on how the Marketing Public Relations strategy using publication, events, information news, and public service activity to attract costumer interest in Grand Elite Hotel Pekanbaru. This research done by the qualitatif research method with the technique used in the data collection is deep interview, observation, and document used. After the data  is collected, then followed by the process of taking note, typing, editing and qualitatif analysis still using words usually arranged into the expanded text. If the collected data is still less then the researcher will do the checking the validity of the data. The result of research shows that the Marketing Public Relations strategy conducted by Grand Elite Hotel are publication events, informations news, and public service activity. In communicating it’s product, Grand Elite Hotel mostly used the promotion. The promotion done by Grand Elite Hotel is using some kind of media. Media used by Grand Elite Hotel to attract costumer interest is printed media, electronic media, and internet media. Special for costumer that usually use the Grand Elite Hotel service, then Grand Elite Hotel will give special price and always build good emotional bond with its costumers. The obstacles that researcher found to attract costumer interest are 1). Internal factor: the lack of creavity in promotion, less strategic place, 2). External factor: consumers taste and competition. Researcher recommended that Marketing Public Relations strategy can go better in the future, thus require the Grand Elite Hotel to run all the Marketing Public Relations strategy with more constructed. Key words: marketing public relations, interest, costumers